2016
DOI: 10.1093/cid/ciw331
|View full text |Cite
|
Sign up to set email alerts
|

A Single-dose Zoledronic Acid Infusion Prevents Antiretroviral Therapy–induced Bone Loss in Treatment-naive HIV-infected Patients: A Phase IIb Trial

Abstract: Background. Human immunodeficiency virus (HIV) infection and antiretroviral therapy (ART) are associated with bone loss leading to increased fracture rate among HIV-infected individuals. ART-induced bone loss is most intense within the first 48 weeks of therapy, providing a window for prophylaxis with long-acting antiresorptives.Methods. In a phase 2, double-blind, placebo-controlled trial, we randomized 63 nonosteoporotic, ART-naive adults with HIV initiating ART with atazanavir/ritonavir + tenofovir/emtricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…Clinical trials have shown smaller reductions in BMD with co-administration of anti-resorptive therapy, such as zolendronate, and calcium and vitamin D supplementation in HIV-infected patients who were starting antiretroviral therapy [20,21]. In this case, the patient had been compliant with her anti-resorptive therapy and vitamin D and calcium supplementation, which may have ameliorated any negative impacts of FTC/TDF on her BMD.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical trials have shown smaller reductions in BMD with co-administration of anti-resorptive therapy, such as zolendronate, and calcium and vitamin D supplementation in HIV-infected patients who were starting antiretroviral therapy [20,21]. In this case, the patient had been compliant with her anti-resorptive therapy and vitamin D and calcium supplementation, which may have ameliorated any negative impacts of FTC/TDF on her BMD.…”
Section: Discussionmentioning
confidence: 97%
“…As a proof of concept, zoledronic acid was demonstrated to ameliorate bone loss associated with T-cell reconstitution in mice, without evidence of impediment to early T-cell reconstitution 97 . The results of a phase II clinical study to test this concept of prophylaxis against bone loss in treatment naive HIV-infected patients initiating cART have now been published 98 . These data reveal that a single administration of zoledronic acid significantly protect patients through the first 48 weeks, the period when ART-induced bone loss is most pronounced, at the lumbar spine, hip and femoral neck 98 .…”
Section: Pathological Bone Turnovermentioning
confidence: 99%
“…In a meta-analysis of the effects of bisphosphonates in HIV-infected patients with low BMD, a mean increase in BMD of 2.85% at the lumbar spine, 1.18% at the femoral neck, and 2.12% at the total hip was seen at 48 weeks [121]. Interestingly, in a phase IIb trial of viremic, cART-naïve, HIV-infected patients without osteoporosis, our group demonstrated that a single infusion of zoledronic acid at the start of therapy with TDF/FTC + ATV/RTV prevented BMD loss at the lumbar spine, hip and femoral neck at 48 weeks [122••]. Although the long-term effects of bisphosphonates in the HIV population on clinically important outcomes such as fracture remain to be determined, these data are promising.…”
Section: Management Of Hiv-associated Bone Lossmentioning
confidence: 99%